Experience in Developing Legislation to Support South Africa's Mandatory GHG Emissions Reporting Program and National Inventory Data Flow - Partnership for Market Readiness (World Bank, Washington, DC, 2018)
South Africa's National Climate Change Response Policy (NCCRP) sets out a number of key goals. Reaching these goals will enable South Africa to meet its commitments under the United Nations Framework Convention on Climate Change (UNFCCC). They key elements that will ensure South Africa can effectively track and steer greenhouse has (GHG) emissions and removals are the following: Establishment of a national system for GHG measurement, reporting and verification (MRV). Meeting UNFCCC reporting commitments on steps taken and envisaged to implement the UNFCCC (focusing on understanding and driving down GHG concentration trends). Integration of these MRV activities with established South Africa systems for Air Pollution Management.